The cartography of the Republican Army General Staff during the Spanish Civil War. The files of general General Vicente Rojo - Nadal, Francesc; Villanova, José Luis (Documents d’Anàlisi Geogràfica, 2011)
During the last years, a great effort of analysis and cataloging of the military maps, plans, sketch and panoramic views elaborated during the civil war has been carried out. With everything, still there are multiple questions for investigating. In this article, is analysed the cartographical training of the general Vicente Rojo, chief of the General Staff of the Republican Army, the relations between this general and the military cartography during the Spanish Civil War, and the military map collection of his personal archive, today preserved in the Archivo Histórico Nacional of Madrid. This map collection possesses a great cartographic and military value, because was used by the General Staff of the Republican Army during the period in that Rojo was at the head of the same one. And, also, in order that contains a series of unedited handwritten cartographic documents of great importance for to understand the development of some of the main bellicose operations of the Spanish Civil War.